Epidemiology, Antifungal Susceptibility, and Pathogenicity of Candida africana Isolates from the United Kingdom - Borman, Andrew M. (American Society for Microbiology, 2013)
Candida africana was previously proposed as a new species within the Candida albicans species complex, together with C. albicans and C. dubliniensis, although further phylogenetic analyses better support its status as an unusual variant within C. albicans. Here we show that C. africana can be distinguished from C. albicans and C. dubliniensis by pyrosequencing of a short region of ITS2, and we have evaluated its occurrence in clinical samples by pyrosequencing all presumptive isolates of C. albicans submitted to the Mycology Reference Laboratory over a 9-month period. The C. albicans complex constituted 826/1,839 (44.9%) of yeast isolates received over the study period and included 783 isolates of C. albicans, 28 isolates of C. dubliniensis, and 15 isolates of C. africana. In agreement with previous reports, C. africana was isolated exclusively from genital specimens, in women in the 18-to-35-year age group. Indeed, C. africana constituted 15/251 (6%) of “C. albicans” isolates from female genital specimens during the study period. C. africana isolates were germ tube positive, grew significantly more slowly than C. albicans and C. dubliniensis on conventional mycological media, could be distinguished from the other members of the C. albicans complex by appearance on chromogenic agar, and were incapable of forming chlamydospores. Here we present the detailed evaluation of epidemiological, phenotypic, and clinical features and antifungal susceptibility profiles of United Kingdom isolates of C. africana. Furthermore, we demonstrate that C. africana is significantly less pathogenic than C. albicans and C. dubliniensis in the Galleria mellonella insect systemic infection model.